1984
DOI: 10.1159/000124023
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Hippocampal Serotonin and the Pituitary-Adrenal Axis in the Septal Driving of Hippocampal Theta-Rhythm

Abstract: Stimulation of the septal area at a frequency between 6 and 10 Hz is able to drive hippocampal theta. In freely moving male rats, the minimum threshold current for driving theta occurs at 7.7 Hz. Disruption of the pituitary-adrenal axis by injection of corticosterone to normal rats or by bilateral adrenalectomy (ADX) causes a shift of the minimum theta-driving threshold to 6.9 Hz. Corticosterone injection to ADX rats returns the minimum to 7.7 Hz. Specific and localized removal of hippocampal serotonergic fibe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

1985
1985
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…Furthermore, though chronic antidepressant administration may atte nuate corticosterone release to stress [31] (not tested in this study), some [28,29], though not all [23], reports sug gest that even major changes in glucocortioid levels have little effect per se on hippocampal corticosteroid receptor mRNA expression [28,29], Whether the action of antide pressants is mediated directly on hippocampal neurons [11,13,16], or indirectly, as shown by imipramine-induced alterations of GR immunoreactivity in mono amine-containing brain stem nuclei [32], is unknown.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Furthermore, though chronic antidepressant administration may atte nuate corticosterone release to stress [31] (not tested in this study), some [28,29], though not all [23], reports sug gest that even major changes in glucocortioid levels have little effect per se on hippocampal corticosteroid receptor mRNA expression [28,29], Whether the action of antide pressants is mediated directly on hippocampal neurons [11,13,16], or indirectly, as shown by imipramine-induced alterations of GR immunoreactivity in mono amine-containing brain stem nuclei [32], is unknown.…”
Section: Discussionmentioning
confidence: 92%
“…The hippocampus receives a dense 5-HTinnervation arising from the raphe nuclei [10] which interacts directly with corticosterone-concentrating cells [11]. In dissociated cultures of fetal hippocampal cells increased 5-HT concentrations lead to elevated glu cocorticoid but not mineralocorticoid binding sites [12], However, results in adult animals in vivo have been less clear-cut.…”
mentioning
confidence: 99%
“…Supporting this hypothesis, neurophysiological data demonstrated that lesions of hippocampal serotoninergic inputs with 5,7-DHT directly affect corticosterone-binding neurons [38]and, more recently, Seckl et al [11]showed that MR mRNA expression in CA3 and CA4 hippocampal areas were reduced in a very similar way 21 days after a global lesion of the serotoninergic system compared to a specific lesion of the serotoninergic inputs to the hippocampus. Finally, Mitchell et al [14]observed a direct stimulatory effect of 5-HT on GR-binding sites in hippocampal primary cell cultures.…”
Section: Discussionmentioning
confidence: 95%
“…The lesion did, however, appear to inhibit the development of tolerance to the effects of nicotine on plasma corticosterone. The data currently available cannot provide an explanation for this observation although it is interesting to note that Azmitia et al (1984) have recently reported that the 5-HTergic fibres which innervate the hippocampus appear to synapse with the neurones which bind corticosterone. These neurones are reported to be involved in the mechanism by which rats terminate the adrenocortical response to a stressful stimulus (Sapolsky et al, 1984).…”
Section: Discussionmentioning
confidence: 96%